The garden and the city : retirement and politics in the later poetry of Pope, 1731-1743. - Mack, Maynard, 1909-2001 (Heritage., 1969)
In this work Mr. Mack explores the tension in Pope's life between Garden and City, between the poet's desire for seclusion and privacy and his concern for political and social issues.